2015
DOI: 10.1371/journal.pone.0128695
|View full text |Cite
|
Sign up to set email alerts
|

Salvia Miltiorrhiza Root Water-Extract (Danshen) Has No Beneficial Effect on Cardiovascular Risk Factors. A Randomized Double-Blind Cross-Over Trial

Abstract: PurposeDanshen is the dried root extract of the plant Salvia Miltiorrhiza and it is used as traditional Chinese medicinal herbal product to prevent and treat atherosclerosis. However, its efficacy has not been thoroughly investigated. This study evaluates the effect of Danshen on hyperlipidemia and hypertension, two well known risk factors for the development of atherosclerosis.MethodsThis was a randomized, placebo-controlled, double-blind crossover study performed at a tertiary referral center. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Six RCTs exploring the efficacy of CHM on one or more of the stroke risk factors were identified in the systematic review. Specifically, one trial examined the ‘CHM plus lifestyle’ intervention for the treatment of ‘IGT and obesity’ compared to ‘placebo plus lifestyle’ intervention, showing significant efficacy on both IGT and obesity before and after treatment and a significant effect on obesity control between groups after treatment [ 58 ]; Two trials examined the ‘CHM plus biomedicine’ interventions for the treatment of ‘diabetes and hyperlipidemia’ and ‘hypertension and hyperlipidemia’ compared to the ‘biomedicine’ intervention [ 59 ] and ‘placebo plus biomedicine’ intervention [ 60 ], respectively—both of these studies found similar effect on the combined stroke risk factors between groups after treatment. Moreover, three trials examined the ‘CHM, biomedicine plus lifestyle’ interventions for the treatment of ‘metabolic syndrome’ [ 61 ], ‘hypertension and metabolic syndrome’ [ 62 ], and ‘hypertension and obesity’ [ 63 ] compared to the ‘biomedicine plus lifestyle’ interventions with or without placebo, respectively, indicating significant effects on all included stroke risk factors by the CHM interventions compared to the control groups after treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six RCTs exploring the efficacy of CHM on one or more of the stroke risk factors were identified in the systematic review. Specifically, one trial examined the ‘CHM plus lifestyle’ intervention for the treatment of ‘IGT and obesity’ compared to ‘placebo plus lifestyle’ intervention, showing significant efficacy on both IGT and obesity before and after treatment and a significant effect on obesity control between groups after treatment [ 58 ]; Two trials examined the ‘CHM plus biomedicine’ interventions for the treatment of ‘diabetes and hyperlipidemia’ and ‘hypertension and hyperlipidemia’ compared to the ‘biomedicine’ intervention [ 59 ] and ‘placebo plus biomedicine’ intervention [ 60 ], respectively—both of these studies found similar effect on the combined stroke risk factors between groups after treatment. Moreover, three trials examined the ‘CHM, biomedicine plus lifestyle’ interventions for the treatment of ‘metabolic syndrome’ [ 61 ], ‘hypertension and metabolic syndrome’ [ 62 ], and ‘hypertension and obesity’ [ 63 ] compared to the ‘biomedicine plus lifestyle’ interventions with or without placebo, respectively, indicating significant effects on all included stroke risk factors by the CHM interventions compared to the control groups after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Except the Bofu - tsusho - san (防风通圣散) used in two trials, all the other CHM interventions involved exploring a combination of multiple stroke risk factors were different and therefore it is unable to report the commonly used Chinese herbs which are vital for the efficacy of combined stroke risk factors across these six RCTs. The sample size of the RCTs focused upon combined stroke risk factors ranged from 20 to 106, and two of these RCTs failed to provide the age and gender profile of participants in the CHM and control groups [ 58 , 60 ]. The duration of the RCTs exploring the combined stroke risk factors ranged from 4 to 6 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In China, S. miltiorrhiza has been widely applied in the treatment of cardiovascular and cerebrovascular diseases (13). Tanshinone IIA is a key active monomer extracted from S. miltiorrhiza (14).…”
Section: Introductionmentioning
confidence: 99%